PEMAKNAAN KOREAN POP CULTURE TERHADAP IDENTITAS BUDAYA (STUDI RESEPSI PADA GAYA HIDUP ANGGOTA KOMUNITAS ART OF DANCE PEKANBARU) - Ika Nurjanah; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The diffusion of Korean Pop Culture that offers various forms of entertainment such as film, drama, variety show, and Korean Music Pop (K-Pop) capture the public’s attention. One of that proofs is the spread of the Korean Wave phenomenon internationally. In the early 2000s, the influences of Korean Pop Culture in Indonesia came through the broadcast from local televisions, which led some of the young generations to make some Korean fan communities in Indonesia, included Pekanbaru city in Riau Province. There many Korean fan communities in Pekanbaru, one of them called by Art of Dance Community. Aside from the performances of AOD’s members, they often mix the language (Indonesian language with Korean language) in daily conversation. Not only in verbal, but also in non verbal, like the way they dress look like Korean. This research was aimed to describe Art of Dance’s member’s reception analysis of Korean Pop Culture toward their cultural identity which can be seen from their lifestyles.This research is descriptive research by using a qualitative approach. This research is using reception analysis which wants to figure out the reception of Korean Pop Culture by Art of Dance’s members in their daily life. The informant of this research are 6 people which are the leader and members of that community. The data in this research were obtained through interviews, observations, and documentation.The result of this study shows that the six informants received the Korean Pop Culture differently, and it can be classified into two meaning positions these are dominant and negotiated. In the outfit styles and non-verbal communication styles, all of 6 members of that community received dominant results, and three of them applied it into their daily life because they want to show their identity as K-Pop fans. In verbal communication, all of informants created a new communication styles, such as mixing the language (Indonesian language with Korean language). In consumption, all of informants received dominant results in consumption of Korean TV Show and things that related to Korea, whereas for consumption of food, informants chose Korean Halal Food. Keywords: Reception Analysis, Korean Pop Culture, Lifestyle